Trespassing the threshold of relevance: Media exposure and opinion polls of the Sweden democrats, 2006-2010 - Pieter Bevelander; Anders Hellström (Institute for the Study of Labor (IZA), 2011)
In September 2010 the anti-immigration party, the Sweden Democrats (SD), crossed the electoral threshold to the Swedish parliament (Riksdagen) for the first time with 5.7 percent of the total votes. The aim of this article is to analyze the effect of the media exposure on fluctuations in opinion polls for political parties; i.e. the media effect. In particular to what extent this can explain the electoral fortunes of the SD. We correlate the number of articles published in the print media with the results of the SD opinion polls as well as the opinion poll results of all the other parliamentary parties during a 48 month period, from the month after the 2006 elections (October 2006) up to September 2010. Our results show that the media effect is more important for the SD compared to the other parliamentary parties, similar in size. The media effect also differs between the six newspapers put into scrutiny in this study, the leading daily Dagens Nyheter (DN) had a considerably stronger effect on the opinion fluctuations, compared to the other five newspapers. To conclude, media exposure sometimes matters, especially for 'new parties', but neither to the same degree everywhere nor at the same time. Ultimately, our findings show that the threshold of relevance does not perfectly match with the crossing of the electoral threshold to the national parliament, as suggested in the literature to explain the electoral fortunes of new anti-immigration parties prior to their entry into parliament.
urn:nbn:de:101:1-201110263493
Keywords: Z10; 330; Populist Radical Right Parties (RPP); The Sweden Democrats (SD); public opinion; opinion polls; Nationalistische Partei; Meinung; Öffentliche Meinung; Zeitung; Medienverhalten; Schweden